Pelatihan Penerapan Layanan Konseling Online Berfokus Solusi Bermuatan Nilai Pancasila pada Guru BK - M Ramli; Nur Hidayah; Diniy Hidayatur Rahman; Nur Mega Aris Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The conditions of problems experienced by students in social media activities after the Covid-19 pandemic are increasingly disappointing. Student problems increase as time goes by and the use of the internet becomes more widespread. The use of the internet in social media has a significant impact on people's social lives. Communication is becoming easier and cheaper so that individuals can obtain information quickly. The dissemination of information and the communication process is one of the important points in the formation of a new phenomenon using social media. One topic of concern is attitudes or behavior of intolerance, hatred, or even racism on social media carried out by teenagers. Based on these conditions, guidance and counseling (BK) teachers in Malang Raya have difficulty choosing an intervention model that suits the characteristics and needs related to the problems they face. So far they have only used counseling or cybercounselling models that were developed based on Western theories, even though there is an obligation for guidance and counseling teachers to help high school students internalize moral values that are in accordance with Indonesian society. Therefore, implementing this training is important to improve the competency of Malang Raya BK teachers in implementing solution-focused online counseling services that include Pancasila values. The training implementation uses a structured learning approach (structured learning approach) combined with a project-based learning approach which is carried out in a combination of offline and online (blended learning) so that the training implementation is more effective with a continuous mentoring system. The implementation of community service in the form of training aims to increase the competency of Malang Raya High School guidance and counseling teachers in implementing cybercounseling or online counseling services focused on solutions to create Pancasila values.